2006
DOI: 10.1007/s10867-006-2670-1
|View full text |Cite
|
Sign up to set email alerts
|

Induced Metastable Memory in Heat Shock Response

Abstract: Abstract. We studied the dynamics of the Heat Shock Response (HSR) mechanism, and the persistence of a injury-protected state in the cell following the shocks, known as thermotolerance. A series of double shock experiments were performed on Chinese Hamster Ovary (CHO) cells, tracking the dynamics of some components of HSR pathway (the Hsp70 protein level and Hsp70 mRNA transcription rate). The main features of HSR dynamics were well reproduced by a simplified model of the chemical reaction pathways governing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Interestingly, Alfieri et al [2006] showed that the effect of ELF-MF on HSF1-HSE binding is really weaker compared to the effect of a conventional stimulus such as heat shock; these results suggest that we cannot exclude that slight changes in Hsp protein expression could take place but we were unable to detect them by Western blot assay. Moreover, if we consider that Hsp consumption after a stress stimulus can occur before the new synthesis [Remondini et al, 2006], a possible slight protein increase induced by ELF-MF could be counterbalanced by an analogue consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Alfieri et al [2006] showed that the effect of ELF-MF on HSF1-HSE binding is really weaker compared to the effect of a conventional stimulus such as heat shock; these results suggest that we cannot exclude that slight changes in Hsp protein expression could take place but we were unable to detect them by Western blot assay. Moreover, if we consider that Hsp consumption after a stress stimulus can occur before the new synthesis [Remondini et al, 2006], a possible slight protein increase induced by ELF-MF could be counterbalanced by an analogue consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of mathematical models describing the heat shock response both in eukaryotes as well as in bacteria have been presented in the literature, see Donati et al (1990); Jones et al (1993); Parsell and Lindquist (1993); Peper et al (1997); Petre et al (2009b); Remondini et al (2006); Rieger et al (2005); Szymańska andŻylicz (2009), still a comprehensive mechanistic understanding of this process is lacking. In Petre et al (2009b) a new model of the eukaryotic heat shock response together with an associated continuous mathematical model based on ordinary differential equations have been discussed.…”
Section: Introductionmentioning
confidence: 99%